The role of agile leadership through commitment on state civil apparatus performance in Palu City - Lestari, Ayu; Hasanuddin, Bakri; Evvy Rossanty, Niluh Putu (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2025)
This study aims to determine the role of agile leadership through commitment to the performance of the state civil apparatus either directly or indirectly. This type of research is descriptive causal which analyzes the main problem regarding Agile Leadership and Female ASN Performance through Mediation of Commitment in Palu City Government. This study used a sample of 164 respondents, the respondents were state civil apparatus led by female leaders in six offices in the Palu City government. The sampling method used the Cluster Area Sampling Method. Hypothesis testing is done with t test and data analysis using Path Anlisys or path analysis test using SPSS 26 software. The results showed that the agile leadership variable had a positive and significant effect on the performance of the State Civil Apparatus in Palu City Government. Agile leadership variable has a positive and significant effect on the commitment of the State Civil Apparatus in Palu City Government. The commitment variable has a positive and significant effect on the performance of the State Civil Apparatus in Palu City Government. Commitment variable does not mediate the effect of agile leadership on the performance of the State Civil Apparatus in Palu City Government.